Sulfur doped graphene quantum dots as a potential sensitive fluorescent probe for the detection of quercetin - Kadian, Sachin; Manik, Gaurav (Food chemistry, 2020)
•Design and synthesis of a novel fluorescent sensing probe.•Quenching in fluorescence of SGQDs by quercetin was explained through the inner filter effect (IFE).•IFE-based fluorescent probe was developed to detect quercetin in real-time red wine samples.•Fluorescent probe exhibited virtues of rapidity, selectivity, simplicity, economic, and high sensitivity. In this work, a novel, selective and sensitive fluorescent probe (sulfur doped graphene quantum dots, SGQDs) was designed for real-time detection of quercetin in red wine samples. SGQDs were synthesized by pyrolyzing citric acid (CA) and 3-Mercaptopropionic acid (MPA) and characterized through advanced techniques. It was observed that fluorescence intensity of SGQDs could be substantially quenched by the addition of quercetin through inner filter effect (IFE) mechanism. Additionally, a visual color change (colorless to light yellow) was also noticed after addition of quercetin into a solution of SGQDs. The change in SGQDs fluorescence intensity with varying quercetin content revealed good linearity in the 0–50.0 μM range with regression coefficient of 0.9943 and a lowest detection limit of 0.006 μg/mL. To authenticate the real-time application of SGQDs as a potential fluorescent probe, red wine samples having different quercetin concentrations were used for quantitative analysis, after the optimization of several analytical parameters.